2022
DOI: 10.1021/acs.iecr.1c04688
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Ionic Liquid Screening Integrating COSMO-RS and Aspen Plus for Selective Recovery of Hydrofluorocarbons and Hydrofluoroolefins from a Refrigerant Blend

Abstract: The selective recovery of hydrofluorocarbons (HFCs) and hydrofluoroolefins (HFOs) from end-of-life equipment is regarded as an efficient and sustainable way for their reclamation, thereby reducing the production and emission of HFCs with high global warming potential. A R454C blend constituted of difluoromethane (R-32) and 2,3,3,3-tetrafluoropropene (R-1234yf) is a nontoxic and mildly flammable refrigerant ideally suitable for hermetically sealed refrigeration systems. This work presents a hierarchical screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…The C and S could be rapid and simple indicators of the extractive potential of DSILs for separating o ‐xylene from n ‐octane. The COSMO‐RS model has been discussed detailedly in previous literatures on its application in calculating various thermodynamic properties 16,31,32,36–41 . It is widely recognized to be able to provide qualitatively reliable and quantitatively acceptable predictions in most cases for the thermodynamic properties of IL‐involved systems, 16,37–40 and therefore is also potentially suitable for estimating the separation performance of DSILs 31,32,41 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C and S could be rapid and simple indicators of the extractive potential of DSILs for separating o ‐xylene from n ‐octane. The COSMO‐RS model has been discussed detailedly in previous literatures on its application in calculating various thermodynamic properties 16,31,32,36–41 . It is widely recognized to be able to provide qualitatively reliable and quantitatively acceptable predictions in most cases for the thermodynamic properties of IL‐involved systems, 16,37–40 and therefore is also potentially suitable for estimating the separation performance of DSILs 31,32,41 .…”
Section: Methodsmentioning
confidence: 99%
“…The COSMO-RS model has been discussed detailedly in previous literatures on its application in calculating various thermodynamic properties. 16,31,32,[36][37][38][39][40][41] It is widely recognized to be able to provide qualitatively reliable and quantitatively acceptable predictions in most cases for the thermodynamic properties of IL-involved systems, 16,[37][38][39][40] and therefore is also potentially suitable for estimating the separation performance of DSILs. 31,32,41 In this work, all COSMO-RS calculations are performed using the COSMOthermX software package (Version 22.0) at the BP86/TZVP level under the BP_TZVP_22.ctd parameterization.…”
Section: Thermodynamic Properties Screeningmentioning
confidence: 99%
“…Recently, an ILs screening method based on COSMO/Aspen Plus was proposed to screen the ILs recovered from R454C for R-32 and R-1234yf. 334 The COSMO-RS model predicted the solubility of R-32 and R-1234yf in 2224 ILs (59 cations and 38 anions) at an infinite dilution. The results showed that ammonium-and phosphonium-based ILs exhibit high solubility, while imidazolium-based ILs exhibit low solubility.…”
Section: Fluoride Ion Effectmentioning
confidence: 99%
“…According to Qin et al, 334 the separation process of a fluorinated refrigerant gas (R-1234yf and R-32) mixture using IL as an absorbent is designed as shown in Figure 21. The designed process flow can achieve the product quality purity of R-1234yf up to 99.5 wt %, and the recovery rate of R-32 will reach 99.0%.…”
Section: Process Design and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation